Propuesta de un modelo para medir activos intangibles en empresas de software a partir de una herramienta multicriterio (2015)
The aim of this paper is to present a proposal for a model to measure and categorize intangible assets in small software companies, from the theoretical foundations of a multi-criteria tool such as the Analytical Hierarchy Process. The methodology consisted of applying the model of measure of intangible assets in three small software companies located in the Technological Park in Cali (Colombia), where the Expert Choice program was used for calculation purposes. According to the results, it is concluded that managers could make decisions related to a continuous improvement process, benchmarking, and even those related to investment and management.